The anti bacterial effect of asian melastome against coagulase-negative staphylococci / Norezzati Aryna Razali - Razali, Norezzati Aryna (Faculty of Applied Sciences, 2017)
Melastoma malabathricum is a scientific name of Asian Melastome, a herbal plant that have been commonly used in folk medicines. This study was carried out with the aim to determine the antimicrobial activity of different concentration of Senduduk ethanol and hexane extract against coagulase-negative staphylococci species, Staphylococcus epidermidis. The antimicrobial effects of both extract were tested against Staphylococcus epidermidis using the disc diffusion method with four different concentration. Result obtained from this study, show no zone of inhibition on both ethanol and hexane extract, suggested that it does not have antimicrobial effects against Staphylococcus epidermidis.